6- Converging Constructions: A Historical Perspective on Sexuality and Feminism in Post-Colonial Africa - Aniekwu, Nkolika Ijeoma (African Sociological Review, 2006)
In recent times, there have been emerging issues on the relevance of the feminist movement in sub-Saharan Africa and the theoretical reconceptualisations that have arisen in response to the discourses on rights, sexuality, roles and identities in the region. Studies have shown that unique factors have a direct bearing on the situation of African women, especially those in post-colonial territories, and that feminist actions in the region are influenced by converging constructs of statehood, culture, religion, politics and ethnicity. Theoretical developments relating to the public/private divide in civil societies provide further contexts in which to analyse African responses to feminism and sexuality. This paper analyses feminism and sexuality in post-colonial Africa as seen from the gendered lens of an African woman. It is a historical perspective of converging constructions that have an impact on the movement in the South, and the colonial dimensions and consequences of these flows on women, rights, identities and roles.